Brazil at the Dawn of the Eighteenth Century. - Antonil, Andre Joao (Classic histories from the Portuguese-speaking world in translation., 2012)
Antonil's great work, recognized as fundamental for understanding the colonial Brazilian economy, now available in its first English translation.